2018
DOI: 10.1111/adb.12638
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens brain‐derived neurotrophic factor (BDNF) transmission inhibits cocaine seeking

Abstract: Brain-derived neurotrophic factor (BDNF) regulates a variety of physiological processes, and several studies have explored the role of BDNF in addiction-related brain regions like the nucleus accumbens core (NAcore). We sought to understand the rapid effects of endogenous BDNF on cocaine seeking. Rats were trained to self-administer cocaine and extinguished. We then microinjected two inhibitors of BDNF stimulation of tropomyosin receptor kinase B (TrkB), the non-competitive receptor antagonist ANA-12 and TrkB/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…These results are consistent with mounting research implicating a role for BDNF in the regulation of drug-related behaviors (Fig. 5;Lu et al 2004;Logrip et al 2009;Vargas-Perez et al 2014;Bobadilla et al 2019;Haun et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with mounting research implicating a role for BDNF in the regulation of drug-related behaviors (Fig. 5;Lu et al 2004;Logrip et al 2009;Vargas-Perez et al 2014;Bobadilla et al 2019;Haun et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Recombinant human BDNF (Sigma-Aldrich, St. Louis, MO, USA) was prepared in aCSF immediately prior to microinfusion. Doses of BDNF were chosen based on previously published reports (Lu et al 2004;Vargas-Perez et al 2014;Bobadilla et al 2019;Haun et al 2018).…”
Section: Bdnf Microinjections and Icsamentioning
confidence: 99%
“…In the NAc, NPAS2 may transcriptionally regulate several key pathways involved in excitatory synaptic homeostasis and plasticity (Ozburn et al, 2015). Our previous findings from NPAS2 ChIP-seq in mouse NAc revealed several strong candidates related to synaptic structure and function, and cocaine reward, including brain derived neurotrophic factor (Bdnf; Graham et al, 2007;Schoenbaum et al, 2007;Heiman et al, 2008;Anderson et al, 2017;Bobadilla et al, 2018), Rho-associated coiled-coilcontaining protein kinase 1 (Rock1; Nakagawa et al, 1996;Henderson et al, 2016), and others which we have recently confirmed, including GABA receptor ␣ 1 (Gabra1; Ozburn et al, 2017). Other intriguing candidates previously linked to cocaine include multiple genes in the nuclear factor -B signaling pathways (Russo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that a high concentration of METH reduces hippocampal LTP (maladaptive plasticity) and neurogenesis, and following it there was extended access expression of BDNF in the hippocampus which is necessary for blocking METH-induced neuronal death [66]. However, some research has focused on direct injection of BDNF into brain nuclei and its effects on search behavior [67]. A previous finding showed injection of doses of toxic METH (high dose, probably) facilitated BDNF synthesis or prevention of degradation of BDNF through dopamine and/ or glutamate receptors [68], which appears to be contrary to our result.…”
Section: Discussionmentioning
confidence: 99%